Effectiveness evaluation of public policy incentive R&D in technological innovation in Brazil: a focus on law of the well - Fernando Zanghelini; Cesar Augusto Souza de Andrade (São Paulo State University (UNESP), 2015)
The present paper will address pharmaceutical industries that carry out research, development and innovation (RD&I) Brazil and their consequent adherence to tax incentives based on 'Law of the Well' (Brazilian, Law No. 11,196 / 2005). Our hypothesis evaluates if public policies of incentives for transformation of technological knowledge could encourage firms to invest in RD&I. Our research was based on Government Annual Reports that reported the use of tax incentives during a period between 2006 and 2012; and legal framework destined for supporting research, both provided by Ministry of Science, Technology and Innovation of Brazil. During the studied period, an increase of 800% of the participating companies of the 'Law of the Well' was observed, demonstrating a need to invest in R&D. The sum of the expenditure of defrayal for the computation of the incentives the companies that operated in real income regime and have chosen to take advantage of tax incentives 'Law of the Well' amounted to R $ 40.52 billion. Well although one of the purposes of the 'Law of the Well' is to subsidize the establishment of researchers in companies, the total value of capital expenditure does not exceed 4% of the total amount invested in R & D activities. Similarly it is observed that the percentage of encouraging the development and patenting did not exceed 1%. In spite of Good Law be used as institutional apparatus for improvement of the efficiency and competitivity of the companies for the global market, recent indicators of spending on R&D in Brazil demonstrate stagnation of investments in various sectors.